PENGARUH KEPEMILIKAN INSTITUSIONAL, INTELLECTUAL CAPITAL, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Saskhia Irving Maest Purba (JAF (Journal of Accounting and Finance), 2019)
The purpose of this study is to determine the influence of institutional ownership (KI), intellectual capital (IC) and Leverage (DER) to financial distress (Springate) financial distress condition. Independent variables in this study are institutional ownership (KI), intellectual capital (IC) and Leverage (DER) and financial distress (Springate) partially or simultaneously. Population in this study is Manufacture companies’s sector listed on Indonesia Stock Exchange in 2014-2017. The sampling technique was using purposive sampling, obtained 128 sample data and use Panel data regression analysis using software Eviews 10. Random effect model was chosen after 3 regression panel test. Simultaneously, all the independet variables have significant effect to dependent variable (financial distress). Partially intellectual capital (IC) have negative significant effect with to financial distress. Leverage (DER) have positive significant effect to financial distress. But institutional ownership (KI) have no significant effect to financial distress. Keyword: Financial distress, Institutional Ownership, Intellectual Capital, Leverage